Battery

By adding fluorophosphate to the electrolyte of lithium-ion batteries and controlling the battery size and content, the risk of fire or explosion caused by thermal runaway of lithium-ion batteries is solved, and a battery with high energy density, long cycle life and high safety performance is achieved .

CN119153789APending Publication Date: 2024-12-17ZHUHAI COSMX BATTERY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411286436.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have the risk of fire or explosion when thermally out of control, and batteries with high energy density and long cycle life have poor safety performance, which is difficult to effectively solve.

Method used

Add specific fluorophosphate esters to the electrolyte, and adjust the size of the battery and the content of the fluorophosphate esters to ensure the uniform distribution of the electrolyte in the battery, reduce the risk of thermal runaway, and improve the safety performance of the battery.

Benefits of technology

The high energy density, long cycle life and high safety performance of lithium-ion batteries have been achieved, and the pass rate of high-temperature cycle stability, hot box testing and overcharge testing has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153789A_ABST
    Figure CN119153789A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a battery. The battery comprises an electrolyte, wherein the electrolyte comprises fluorophosphate; the ratio T / L of the thickness T of the battery to the length L of the battery is 0.05-0.15; the ratio T / W of the thickness T of the battery to the width W of the battery is 0.07-0.2; the length L, the width W and the thickness T of the battery and the mass content C1 of the fluorophosphate in the electrolyte meet the condition that (T * L * W) / (C1 * 100000) is more than or equal to 0.3 and less than or equal to 200. The battery provided by the invention has high energy density and long cycle life, can effectively reduce the occurrence risk of thermal runaway, and has relatively high safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art

[0002] Lithium-ion batteries are widely used in new energy vehicles, mobile devices and energy storage systems due to their high energy density and long cycle life, but the safety issues that come with them cannot be ignored. Lithium-ion batteries may experience thermal runaway in the event of internal short circuits, overcharge / discharge, overheating or physical damage. During thermal runaway, the battery will release a large amount of heat and flammable gases, causing the battery temperature to rise, which in turn causes fire or explosion, posing a serious threat to personal safety. In recent years, in pursuit of higher energy density, the voltage and volume of lithium-ion batteries have gradually increased, making safety issues more significant. Studies have found that safety issues caused by thermal runaway can be improved through many strategies such as improving electrolytes, optimizing electrode materials, improving battery structures, and strengthening monitoring systems. However, the improvement effect is not ideal.

[0003] Therefore, it is very important to invent a battery with high energy density, long cycle life and high safety performance. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem of poor safety performance of batteries with high energy density and long cycle life in the prior art, and provide a battery. The battery of the present invention adds a specific substance to the electrolyte, and by regulating the size of the battery and the relationship between the content of the specific substance and the size of the battery, the battery can have high energy density and long cycle life while reducing the risk of thermal runaway and improving the safety performance of the battery.

[0005] In the related art, the effect of improving the safety performance of batteries with high energy density is not good. The inventors of the present invention have found that the safety performance of the battery can be improved by adding specific fluorophosphates to the electrolyte. This is because: first, the specific fluorophosphates have lower volatility and higher flash point and oxidation resistance, which means that they are more difficult to burn and can work at higher voltages, which is more in line with the development trend of batteries; secondly, the specific fluorophosphates can release phosphorus-oxygen free radicals under high temperature conditions, which not only do not increase the risk of thermal runaway of the battery, but also can capture and consume other free radicals generated by the battery during heat release or combustion, thereby effectively reducing the risk of fire or explosion of the battery when it is overheated or damaged; finally, the specific fluorophosphates will form fluorine- and phosphorus-containing interface products during the battery cycle process, which can improve the mechanical and high temperature stability of the interface film, which is conducive to the improvement of safety performance.

[0006] However, if only specific fluorophosphates are simply added to the electrolyte, the improvement in the safety performance of the battery is limited. The inventors of the present invention have conducted a lot of research and found that the reason why only adding specific fluorophosphates can only improve the safety performance of the battery is that: first, the size of the battery has a greater impact on its safety performance. When the size increases, the heat generated by the battery during the charge and discharge cycle will increase accordingly; and when the size decreases, the specific surface area of ​​the battery increases accordingly. At this time, the external ambient temperature has a greater impact on it. When the battery is in a high temperature environment, the external high temperature is more likely to be transmitted to the inside of the battery, which will also cause thermal runaway. Second, the distribution of the electrolyte in the battery also affects the safety performance of the battery. When the electrolyte is unevenly distributed in the battery, the area with less electrolyte distribution is prone to decomposition due to the lack of electrolyte infiltration, which will not only lead to insufficient battery kinetics, but also increase the risk of thermal runaway. Based on the above findings, the inventors of the present invention have conducted a lot of targeted research and proposed the following technical solutions:

[0007] The present invention provides a battery, the battery comprising an electrolyte, the electrolyte comprising a fluorophosphate ester, the fluorophosphate ester having a structural formula of Wherein R1, R2 and R3 are each independently selected from at least one of the following fluorine-substituted or unsubstituted groups: alkyl, alkenyl, alkynyl and phenyl, and the total number of fluorine substituents in R1, R2 and R3 is ≥3; the ratio T / L of the thickness T of the battery to the length L of the battery is 0.05-0.15; the ratio T / W of the thickness T of the battery to the width W of the battery is 0.07-0.2; the length L (in mm), width W (in mm), thickness T (in mm) of the battery and the mass content C1 of the fluorophosphate in the electrolyte satisfy: 0.3≤(T×L×W) / (C1×100000)≤200.

[0008] The ratio of the thickness to the length and the ratio of the thickness to the width of the battery can reflect the distribution of the electrolyte in the battery to a certain extent. When T / L and T / W are within a specific range, it means that the electrolyte is distributed more evenly in the battery, and the specific fluorophosphate in the electrolyte can effectively protect various areas in the battery. When T / L and T / W exceed the above range, the top, bottom and even near the pole ear of the battery are prone to less electrolyte. At this time, the risk of analysis at these locations will increase significantly, which is not conducive to the safety performance of the battery. However, it is not enough to improve the safety performance by controlling the distribution of the electrolyte in the battery. It is also necessary to coordinate the relationship between the length, width and thickness of the battery and the content of fluorophosphate. The reason is that: first, although fluorophosphate can improve the safety performance of the battery, it has a destructive effect on the SEI film on the surface of the negative electrode. Therefore, in order to ensure the cycle performance of the battery, the content of fluorophosphate needs to be adjusted according to the size of the battery. Second, as mentioned above, the size of the battery has a great influence on its safety performance. When the size is large, the heat inside the battery has a greater impact on its safety performance; when the size is small, the external ambient temperature of the battery has a greater impact on its safety performance. Therefore, different sizes need to be matched with different fluorophosphate contents to make the battery have better overall performance. In summary, by regulating the ratio of battery thickness to length and the ratio of thickness to width, the flow direction of the electrolyte in the battery can be effectively controlled; at the same time, regulating the relationship between the length, width and thickness of the battery and the content of fluorophosphate can effectively improve the battery's high-temperature cycle performance, high-temperature storage performance and the pass rate of hot box test, puncture test and overcharge test.

[0009] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0010] (1) The battery of the present invention has high energy density and cycle stability;

[0011] (2) The battery of the present invention has good high temperature cycle stability and high temperature storage performance;

[0012] (3) The battery of the present invention has good safety performance, and the pass rate of the hot box test, the needle penetration test and the overcharge test is high.

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1FIG. 1 is a schematic diagram of a battery in an embodiment of the present invention, wherein Figure 1 (a) is the front view, Figure 1 (b) is a side view.

[0015] Figure 2 Shown is a schematic structural diagram of a negative electrode current collector in an example of the present invention. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] The present invention provides a battery, which may include an electrolyte. The electrolyte may include fluorophosphate.

[0018] The structural formula of the fluorophosphate can be Among them, R1, R2 and R3 can be independently selected from at least one of the following fluorine-substituted or unsubstituted groups: alkyl, alkenyl, alkynyl and phenyl, and the total number of fluorine substituents in R1, R2 and R3 is ≥3, for example, 3, 4, 5, 6, 7, 8 or 9.

[0019] In the present invention, the total number of fluorine substituents in R1, R2 and R3 can be measured by conventional methods in the art, such as nuclear magnetic resonance (NMR), fluorescent probe method or gas chromatography-mass spectrometry (GC-MS).

[0020] In the present invention, the ratio T / L of the thickness T of the battery to the length L of the battery may be 0.05-0.15, such as 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14 or 0.15. The ratio T / W of the thickness T of the battery to the width W of the battery may be 0.07-0.2, such as 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.2.

[0021] In the present invention, the length L (in mm), width W (in mm), thickness T (in mm) of the battery and the mass content C1 of the fluorophosphate in the electrolyte satisfy: 0.3≤(T×L×W) / (C1×100000)≤200, for example, 0.3, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150 or 200.

[0022] In one example, 11≤(T×L×W) / (C1×100000)≤50.

[0023] In one example, 15≤(T×L×W) / (C1×100000)≤45.

[0024] When (T×L×W) / (C1×100000) is too large (for example, greater than 200), the size of the battery is large relative to the content of fluorophosphate. At this time, the content of fluorophosphate is relatively small, and the occurrence of battery thermal runaway cannot be effectively alleviated; and when (T×L×W) / (C1×100000) is too small (for example, less than 0.3), the size of the battery is small relative to the content of fluorophosphate. At this time, the content of fluorophosphate is relatively high, and excessive fluorophosphate has an adverse effect on the negative electrode sheet, which is not conducive to the cycle stability of the battery.

[0025] In one example, T / L is 0.7-0.14.

[0026] In one example, T / W is 0.08-0.18.

[0027] In the present invention, the thickness T of the battery can be 2-12, in units of mm, for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12. When the thickness T of the battery is small (for example, less than 2 mm), the thickness of the battery is too small, the strength and hardness of the battery are insufficient, and the manufacturing process is more difficult; and when the thickness T of the battery is large (for example, greater than 12 mm), the thickness of the battery is too large, which may lead to uneven internal heat distribution, which is not conducive to improving safety performance.

[0028] In the present invention, the length L of the battery can be 20-220, in mm, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210 or 220. When the length L of the battery is small (for example, less than 20 mm), the length of the battery is too short, resulting in insufficient energy density; and when the length L of the battery is large (for example, greater than 220 mm), the length of the battery is too long, resulting in uneven current transfer inside the battery and reduced cycle stability of the battery.

[0029] In the present invention, the width W of the battery may be 15-125, in units of mm, for example, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120 or 125. When the width W of the battery is small (for example, less than 15 mm), the width of the battery is too small, resulting in an increased risk of tab short circuit; and when the width W of the battery is large (for example, greater than 125 mm), the width of the battery is too large, at which time the utilization rate of the active material is reduced and the risk of edge analysis is increased.

[0030] like Figure 1 FIG. 1 is a schematic diagram of a battery in an embodiment of the present invention, wherein Figure 1 (a) is the front view, Figure 1 (b) is a side view. It can be seen from the figure that the length of the battery is L, the width is W, and the thickness is T.

[0031] In the present invention, the mass content C1 of the fluorophosphate in the electrolyte may be 0.5%-5%, for example, 0.5%, 1%, 2%, 3%, 4% or 5%.

[0032] In one example, the mass content C1 of the fluorophosphate in the electrolyte is 1%-3%.

[0033] When the mass content of fluorophosphate in the electrolyte is too small (for example, less than 0.5%), the content of fluorophosphate in the electrolyte is too low, and the overall high-temperature stability of the electrolyte cannot be effectively improved, which is not conducive to the improvement of the high-temperature performance and safety performance of the battery; and when the mass content of fluorophosphate in the electrolyte is too large (for example, greater than 5%), the content of fluorophosphate in the electrolyte is too high. Since the viscosity of the fluorophosphate itself is too high, the overall viscosity of the electrolyte will increase, which is not conducive to the charge and discharge efficiency of the battery; and, excessive fluorophosphate will damage the negative electrode sheet and affect the cycle stability of the battery.

[0034] In the present invention, the mass content C1 of the fluorophosphate in the electrolyte can be measured by conventional methods in the art, such as GC-MS.

[0035] In one example, R1, R2 and R3 are each independently selected from at least one of the following fluorine-substituted groups: an alkyl group having 1 to 3 carbon atoms, an alkenyl group having 2 or 3 carbon atoms, an alkynyl group having 2 or 3 carbon atoms, and a phenyl group.

[0036] In one example, the fluorophosphate comprises

[0037] At least one of .

[0038] In one example, the fluorophosphate comprises

[0039] The inventors of the present invention have discovered that specific fluorophosphates not only have higher oxidation resistance and thermal stability, but also have an interaction force with unstable solvents such as carbonates, thereby being able to anchor unstable solvents in the electrolyte and prevent such solvent molecules from violently moving and decomposing at high temperatures, thereby achieving an improvement in the overall antioxidant capacity and thermodynamic stability of the electrolyte, which can further delay the occurrence of thermal runaway and improve the safety performance of the battery.

[0040] In the present invention, the battery may further include a negative electrode sheet, and the negative electrode sheet may include a negative electrode current collector. The negative electrode current collector may include a polymer layer and a metal layer located on both sides of the polymer layer. Figure 2 The figure shows a schematic structural diagram of a negative electrode current collector in an example of the present invention. It can be seen from the figure that the negative electrode current collector includes a polymer layer 1 and metal layers 2 located on both sides of the polymer layer 1.

[0041] Since the electrolyte will produce hydrofluoric acid during the battery charge and discharge cycle, and hydrofluoric acid has a strong corrosive effect on the positive electrode collector and the negative electrode collector. In addition, since fluorophosphate has a damaging effect on the SEI film on the surface of the negative electrode sheet, the hydrofluoric acid generated in the electrolyte is particularly corrosive to the negative electrode collector. Therefore, in order to further improve the safety performance of the battery, the negative electrode collector can be specially designed to alleviate the damage of hydrofluoric acid to the negative electrode collector. The negative electrode collector is set to a "sandwich" structure, and a metal layer is set on both sides of the polymer layer. The polymer layer in the middle has a strong flame retardant property, which is conducive to alleviating the occurrence of thermal runaway of the battery; and it is not easy to short-circuit when the battery is mechanically damaged, which is conducive to improving the overall safety performance of the battery. In addition, the oxygen-containing functional group in the molecular structure of fluorophosphate has a certain adsorption effect on the hydrofluoric acid in the electrolyte, and can also reduce the corrosion of the electrolyte to the negative electrode collector to a certain extent, prevent the metal layer and the polymer layer from delithiation, thereby affecting the conductive performance of the negative electrode sheet. Therefore, the battery of the present invention can improve the charge and discharge performance while ensuring good safety performance by further designing the negative electrode current collector.

[0042] In one example, the polymer layer includes at least one of polypropylene, polyethylene, polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyvinyl chloride, polyethylene terephthalate, polypropylene, and polyimide.

[0043] In one example, the metal layer includes copper.

[0044] In the present invention, the thickness of the polymer layer may be 1 μm-10.5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or 10.5 μm.

[0045] In one example, the polymer layer has a thickness of 2 μm-5.5 μm.

[0046] In the present invention, the thickness of the metal layer may be 0.3 μm-4.5 μm, for example, 0.3 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 4.5 μm.

[0047] In one example, the thickness of the metal layer is 0.5 μm-2.5 μm.

[0048] The specific polymer layer thickness and / or metal layer thickness can ensure that the battery has a higher energy density while having better safety performance.

[0049] In the present invention, the thickness of the metal layer refers to the thickness of a single layer of the metal layer.

[0050] In the present invention, the negative electrode sheet may further include a negative electrode active material layer, and the negative electrode active material layer may be located on at least one side surface of the negative electrode current collector.

[0051] In one example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the surface of the negative electrode current collector.

[0052] In the present invention, the negative electrode active material layer may contain element Si. The mass content of element Si in the negative electrode active material layer may be 0.02%-50%, for example, 0.02%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%. And the battery may also include an aluminum-plastic film, and the thickness of the aluminum-plastic film may be 20μm-120μm, for example, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm or 120μm.

[0053] In one example, the mass content of the element Si in the negative electrode active material layer is 0.02%-30%, and the thickness of the aluminum-plastic film can be 20 μm-120 μm.

[0054] In one example, the mass content of the element Si in the negative electrode active material layer is 0.05%-10%, and the thickness of the aluminum-plastic film is 35 μm-105 μm.

[0055] In order to improve the energy density of the battery, silicon-based materials are usually added to the negative electrode active material, but the silicon-based material will have a large volume expansion problem during the battery charge and discharge cycle, which is not conducive to the cycle stability of the battery. The fluorophosphate of the battery of the present invention has a certain degree of damage to the SEI film on the surface of the negative electrode sheet, and the SEI film can limit the expansion of the silicon-based material to a certain extent. Therefore, it is necessary to limit the content of element Si in the negative electrode active material layer, so as to avoid the excessive volume expansion of the silicon-based material and cause the decline of the battery cycle stability. At the same time, the thickness of the aluminum-plastic film is limited to coordinately improve the cycle stability of the battery. The aluminum-plastic film usually has a three-layer structure, the outermost layer is a nylon layer, the middle layer is an aluminum layer, and the innermost layer is a polypropylene (PP) layer. Fluorophosphate not only does not react chemically with the inner layer of the aluminum-plastic film, but can also be inserted between the polymer molecular chains in the inner layer of the aluminum-plastic film through swelling, thereby enhancing the mobility of the molecular chain and improving the flexibility of the inner layer of the aluminum-plastic film. Fluorophosphates can enhance the tensile stress of aluminum-plastic films. Under the premise of a specific silicon content, they can effectively inhibit problems such as corner cracks in the aluminum-plastic film caused by the volume expansion of silicon-based materials, which is beneficial to improving the cycle stability of the battery.

[0056] When the mass content of element Si in the negative electrode active material layer is too low (e.g., less than 0.02%), the battery energy density is insufficiently improved; when the mass content of element Si in the negative electrode active material layer is too high (e.g., greater than 50%), the volume expansion of the silicon-based material is too large, resulting in an increase in interface side reactions and an increase in the total thickness of the battery. When the thickness of the aluminum-plastic film is too thin (e.g., less than 20 μm), the thickness of the aluminum-plastic film is insufficient, which can easily lead to battery cracking or wrinkling, affecting the battery's cycle stability; and when the thickness of the aluminum-plastic film is too thick (e.g., greater than 120 μm), it is not conducive to the battery's energy density and cell heat dissipation, and is not conducive to high temperature performance.

[0057] In one example, the mass content of the element Si in the negative electrode active material layer is 0.05%-10%.

[0058] In the present invention, the mass content of the element Si in the negative electrode active material layer can be tested by conventional methods in the art, such as disassembling the battery, taking out the negative electrode sheet, scraping the negative electrode active material layer, performing ashing and acid dissolution treatment, and then testing using inductively coupled plasma emission spectroscopy.

[0059] In one example, the thickness of the aluminum-plastic film is 35 μm-105 μm.

[0060] In the present invention, the negative electrode active material layer may include a negative electrode conductive agent. The negative electrode conductive agent may include carbon nanotubes. The aspect ratio of the carbon nanotubes may be 50-3000, for example, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000 or 3000.

[0061] In one example, the aspect ratio of the carbon nanotubes is 500-2500.

[0062] The inventors of the present invention have found that when the aspect ratio of carbon nanotubes is within a specific range, carbon nanotubes can form an effective conductive network in the electrode sheet, thereby improving the transmission rate of electrons. The use of carbon nanotubes in the negative electrode sheet of the present invention is beneficial to improving the overall charge and discharge efficiency and cycle stability of the battery. This is because fluorophosphates, due to their high viscosity, will increase the overall viscosity of the electrolyte and reduce the conductivity, resulting in uneven local transmission of the negative electrode sheet during low-temperature cycles, causing lithium precipitation. Using carbon nanotubes with a specific aspect ratio as a conductive agent can alleviate the adverse effects of fluorophosphates on conductivity. In addition, the conductive network formed by carbon nanotubes in the negative electrode sheet is beneficial to improving the overall mechanical strength of the negative electrode sheet, and has a certain inhibitory effect on the volume expansion of silicon-based materials, which is beneficial to the cycle stability of the battery.

[0063] In the present invention, the aspect ratio of the carbon nanotubes can be tested by conventional methods in the art, for example, using a scanning electron microscope (SEM), taking a negative electrode sheet for scanning, taking a field of view at random, randomly selecting at least 20 carbon nanotubes within the field of view, measuring the tube length and outer diameter of each carbon nanotube, respectively, calculating the aspect ratio of each carbon nanotube, and taking an average value.

[0064] In the present invention, the carbon nanotubes in the negative electrode conductive agent include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0065] In the present invention, the negative electrode active material layer may further include a negative electrode active material, and the negative electrode active material may include a silicon-based material. The silicon-based material may include at least one of silicon carbon, silicon oxygen, nano silicon and silicon alloy.

[0066] In the present invention, the specific surface area of ​​the silicon-based material can be 0.4 m 2 / g-15m 2 / g, for example 0.4m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g or 15m 2 / g.

[0067] In one example, the specific surface area of ​​the silicon-based material is 2 m 2 / g-5m 2 / g.

[0068] The inventors of the present invention have found that when the specific surface area of ​​the silicon-based material is within a specific range, it is beneficial for the oxygen-containing functional groups in the fluorophosphate to be adsorbed on active sites such as -OH and -COOH on the surface of the silicon-based material (such as silicon carbon), thereby preventing these active sites from having side reactions with other components in the electrolyte, consuming the electrolyte, and causing a decrease in the electrical performance of the battery.

[0069] In the present invention, the specific surface area of ​​the silicon-based material can be measured by conventional methods in the art, such as a specific surface area and porosity analyzer.

[0070] In the present invention, the negative electrode active material may further include a carbon-based material, and the carbon-based material may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, and hard carbon.

[0071] In one example, the negative electrode conductive agent may further include at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, and conductive carbon fiber.

[0072] In the present invention, the negative electrode active material layer may further include a negative electrode binder, and the negative electrode binder may include at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide.

[0073] In the present invention, based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 80-99.8 weight % (for example, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 99 or 99.8 weight %), the content of the negative electrode conductor can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %), and the content of the negative electrode binder can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %).

[0074] In the present invention, the battery may further include a positive electrode sheet. The positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector. The positive electrode active material layer may include a positive electrode conductive agent. The positive electrode conductive agent may include carbon nanotubes. The aspect ratio of the carbon nanotubes may be 50-3000, for example, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000 or 3000.

[0075] In one example, the aspect ratio of the carbon nanotubes is 500-2500.

[0076] As mentioned above, carbon nanotubes with a specific aspect ratio can form an effective conductive network in the electrode, thereby improving the electron transmission rate. Therefore, when both the positive electrode and the negative electrode use carbon nanotubes with a specific aspect ratio as a conductive agent, the electron transmission rate of the battery can be improved as a whole.

[0077] In the present invention, the testing method of the aspect ratio of the carbon nanotubes in the positive electrode sheet is the same as that of the aspect ratio of the carbon nanotubes in the negative electrode sheet.

[0078] In the present invention, the carbon nanotubes in the positive electrode conductive agent include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0079] In the present invention, the positive electrode active material layer may further include a positive electrode active material and a positive electrode binder. The positive electrode active material may include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate and lithium-rich manganese-based materials. The positive electrode binder may include at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide.

[0080] In one example, the positive electrode conductive agent may further include at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, and conductive carbon fiber.

[0081] In the present invention, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be 80-99.8 weight % (for example, 80, 82, 84, 86, 88, 90, 92, 94, 96, 98, 99 or 99.8 weight %), the content of the positive electrode conductor can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %), and the content of the positive electrode binder can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %).

[0082] In the present invention, the electrolyte may further include a fluorinated cyclic carbonate. The mass content of the fluorinated cyclic carbonate in the electrolyte is C2, and C1 / C2 may be 0.04-0.5, for example, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4 or 0.5.

[0083] In one example, C1 / C2 is 0.15-0.2.

[0084] Since fluorinated cyclic carbonates have a good protective effect on the SEI film on the surface of the negative electrode sheet, when the content ratio of the two is within a specific range, fluorinated cyclic carbonates can effectively alleviate the damage of fluorinated phosphates to the SEI film, which is beneficial to improving the battery cycle stability.

[0085] In one example, the fluorinated cyclic carbonate includes at least one of fluoroethylene carbonate and bisfluoroethylene carbonate.

[0086] In the present invention, the mass content C2 of the fluorinated cyclic carbonate in the electrolyte can be 5%-20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0087] In one example, the mass content C2 of the fluorinated cyclic carbonate in the electrolyte is 6%-15%.

[0088] In the present invention, the mass content C2 of the fluorinated cyclic carbonate in the electrolyte can be measured by conventional methods in the art, such as GC-MS.

[0089] In the present invention, the electrolyte may further include an organic solvent. The organic solvent may include a carbonate solvent and / or a carboxylate solvent, and the carbonate solvent may include ethylene carbonate and at least one of the following solvents substituted or unsubstituted with fluorine: propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The carboxylate solvent may include at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, propyl propionate, ethyl propionate, and methyl butyrate.

[0090] In the present invention, the mass content of the organic solvent in the electrolyte is less than or equal to 80%, for example, 80%, 70%, 60%, 50% or 40%.

[0091] In the present invention, the electrolyte may further include a lithium salt, which may include at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium tetrafluoroborate.

[0092] In the present invention, the mass content of the lithium salt in the electrolyte may be 12%-18%, for example, 12%, 13%, 14%, 15%, 16%, 17% or 18%.

[0093] In the present invention, the electrolyte may further include an additive. The additive may include at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,3,4,5,6-(2-cyanoethoxy)hexane, 1,3-propanesultone, propylene-1,3sultone, and vinyl sulfite.

[0094] In the present invention, the mass content of the additive in the electrolyte may be 3%-12%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12%.

[0095] Nitrile additives can complex metal ions dissolved from the positive electrode side and improve the stability of the positive electrode active material. Cyclic sulfonate additives can improve the interface film, and the sulfur in them can also improve the ion conductivity of the CEI film, thereby improving the overall performance of the battery.

[0096] In the present invention, the applied voltage of the battery is greater than or equal to 4.45 V. The battery of the present invention can effectively improve the safety problem caused by the increase of battery volume under high voltage conditions.

[0097] In the present invention, the battery may further include a separator, and the separator may be a separator conventionally used in the art.

[0098] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0099] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0100] The following examples are provided to illustrate the batteries of the present invention.

[0101] Example 1

[0102] Prepare the battery as follows:

[0103] (1) Preparation of positive electrode sheet

[0104] Lithium cobalt oxide, polyvinylidene fluoride (PVDF 500), Super P and carbon nanotubes (aspect ratio of 1523) are mixed evenly in a mass ratio of 97:2:0.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is continuously stirred in a stirrer to form a uniform and flowing positive electrode slurry; the positive electrode slurry is coated on an aluminum foil with a thickness of 8 μm, and dried in a vacuum oven at 120°C for 6 hours, and then rolled and cut to obtain a positive electrode sheet.

[0105] (2) Preparation of negative electrode sheet

[0106] Artificial graphite, silicon carbon (specific surface area 3.75m 2 / g), Super P, carbon nanotubes (aspect ratio of 1523), sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 86.2:11.8:0.5:0.5:0.5:0.5, deionized water is added, and the mixture is continuously stirred by a stirrer to form a uniform and flowing negative electrode slurry; the negative electrode slurry is coated on the surface of the negative electrode current collector (a polyethylene terephthalate film with a thickness of 3.2 μm and a copper metal layer with a thickness of 1.2 μm on both sides respectively), and then dried in a vacuum oven at 120°C for 6 hours, and then rolled and cut to obtain a negative electrode sheet, wherein the mass content of element Si in the negative electrode active material layer is 5.3%.

[0107] (3) Preparation of electrolyte

[0108] In a glove box filled with argon (water content <1ppm, oxygen content <1ppm), ethylene carbonate, propylene carbonate, propyl propionate and ethyl propionate are mixed into a uniform solvent in a mass ratio of 15:15:50:20, and 15% of lithium hexafluorophosphate based on the total mass of the electrolyte is slowly added thereto, followed by 3% of 1,3-propane sultone and 4% of 1,3,6-hexanetrinitrile based on the total mass of the electrolyte, and then 12% of fluoroethylene carbonate and 2.2% of fluorophosphate ester I-1 based on the total mass of the electrolyte are added; after stirring evenly, an electrolyte is obtained in which C1 / C2 is approximately 0.18.

[0109] (4) Preparation of batteries

[0110] The positive electrode sheet prepared in step (1), the separator (a polyethylene substrate with a thickness of 8 μm and a polyvinylidene fluoride and boehmite mixed layer with a thickness of 2 μm respectively coated on both sides) and the negative electrode sheet prepared in step (2) are wound to prepare a bare battery cell; the bare battery cell is placed in an aluminum-plastic film (with a thickness of 52 μm), and the electrolyte prepared in step (3) is injected into the dried bare battery cell, and a battery is obtained after vacuum packaging, room temperature aging, high temperature formation and other processes, wherein the thickness T of the battery is 8.5 mm, the length L is 120.2 mm, and the width W is 95 mm. The relevant parameters are specifically shown in Table 1.

[0111] Example 2

[0112] Prepare the battery as follows:

[0113] (1) Preparation of positive electrode sheet

[0114] Lithium cobalt oxide, polyvinylidene fluoride (PVDF 500), Super P and carbon nanotubes (aspect ratio of 508) are mixed evenly in a mass ratio of 97:2:0.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is continuously stirred in a stirrer to form a uniform and flowing positive electrode slurry; the positive electrode slurry is coated on an aluminum foil with a thickness of 8 μm, and dried in a vacuum oven at 120°C for 6 hours, and then rolled and cut to obtain a positive electrode sheet.

[0115] (2) Preparation of negative electrode sheet

[0116] Artificial graphite, silicon carbon (specific surface area of ​​4.32m 2 / g), Super P, carbon nanotubes (aspect ratio of 508), sodium carboxymethyl cellulose and styrene-butadiene rubber are evenly mixed in a mass ratio of 86.2:11.8:0.5:0.5:0.5:0.5, deionized water is added, and the mixture is continuously stirred in a stirrer to form a uniform and flowing negative electrode slurry; the negative electrode slurry is coated on the surface of the negative electrode current collector (a polypropylene film with a thickness of 2.1 μm has a copper metal layer with a thickness of 2.3 μm on both sides respectively), and then dried in a vacuum oven at 120°C for 6 h, and then rolled and cut to obtain a negative electrode sheet, wherein the mass content of element Si in the negative electrode active material layer is 5.1%.

[0117] (3) Preparation of electrolyte

[0118] In a glove box filled with argon (water content <1ppm, oxygen content <1ppm), ethylene carbonate, propylene carbonate, propyl propionate and ethyl propionate are mixed into a uniform solvent in a mass ratio of 15:15:50:20, and 15% of lithium hexafluorophosphate based on the total mass of the electrolyte is slowly added thereto, followed by 3% of 1,3-propane sultone and 4% of 1,3,6-hexanetrinitrile based on the total mass of the electrolyte, and then 6% of fluoroethylene carbonate and 1% of fluorophosphate ester I-1 based on the total mass of the electrolyte are added; after stirring evenly, an electrolyte is obtained in which C1 / C2 is approximately 0.17.

[0119] (4) Preparation of batteries

[0120] The positive electrode sheet prepared in step (1), the separator (a polyethylene substrate with a thickness of 8 μm and a polyvinylidene fluoride and boehmite mixed layer with a thickness of 2 μm respectively coated on both sides) and the negative electrode sheet prepared in step (2) are wound to prepare a bare battery cell; the bare battery cell is placed in an aluminum-plastic film (with a thickness of 83 μm), and the electrolyte prepared in step (3) is injected into the dried bare battery cell, and a battery is obtained through vacuum packaging, room temperature aging, high temperature formation and other processes, wherein the thickness T of the battery is 6.2 mm, the length L is 85.5 mm, and the width W is 64.6 mm. The relevant parameters are specifically shown in Table 1.

[0121] Example 3

[0122] Prepare the battery as follows:

[0123] (1) Preparation of positive electrode sheet

[0124] Lithium cobalt oxide, polyvinylidene fluoride (PVDF 500), Super P and carbon nanotubes (aspect ratio of 2496) are mixed evenly in a mass ratio of 97:2:0.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is continuously stirred in a stirrer to form a uniform and flowing positive electrode slurry; the positive electrode slurry is coated on an aluminum foil with a thickness of 8 μm, and dried in a vacuum oven at 120°C for 6 hours, and then rolled and cut to obtain a positive electrode sheet.

[0125] (2) Preparation of negative electrode sheet

[0126] Artificial graphite, silicon carbon (specific surface area of ​​2.86m 2 / g), Super P, carbon nanotubes (aspect ratio of 2496), sodium carboxymethyl cellulose and styrene-butadiene rubber are evenly mixed in a mass ratio of 86.2:11.8:0.5:0.5:0.5:0.5, deionized water is added, and the mixture is continuously stirred by a stirrer to form a uniform and flowing negative electrode slurry; the negative electrode slurry is coated on the surface of the negative electrode current collector (a polyimide film with a thickness of 5.1 μm and a copper metal layer with a thickness of 0.5 μm on both sides respectively), and then dried in a vacuum oven at 120°C for 6 hours, and then rolled and cut to obtain a negative electrode sheet, wherein the mass content of element Si in the negative electrode active material layer is 5.6%.

[0127] (3) Preparation of electrolyte

[0128] In a glove box filled with argon (water content <1ppm, oxygen content <1ppm), ethylene carbonate, propylene carbonate, propyl propionate and ethyl propionate are mixed into a uniform solvent in a mass ratio of 15:15:50:20, and 15% of lithium hexafluorophosphate based on the total mass of the electrolyte is slowly added thereto, followed by 3% of 1,3-propane sultone and 4% of 1,3,6-hexanetrinitrile based on the total mass of the electrolyte, and then 15% of fluoroethylene carbonate and 3% of fluorophosphate ester I-1 based on the total mass of the electrolyte are added; after stirring evenly, an electrolyte is obtained in which C1 / C2 is approximately 0.2.

[0129] (4) Preparation of batteries

[0130] The positive electrode sheet prepared in step (1), the separator (a polyethylene substrate with a thickness of 8 μm and a polyvinylidene fluoride and boehmite mixed layer with a thickness of 2 μm respectively coated on both sides) and the negative electrode sheet prepared in step (2) are wound to prepare a bare battery cell; the bare battery cell is placed in an aluminum-plastic film (with a thickness of 96 μm), and the electrolyte prepared in step (3) is injected into the dried bare battery cell, and a battery is obtained through vacuum packaging, room temperature aging, high temperature formation and other processes, wherein the battery has a thickness T of 10.5 mm, a length L of 75.9 mm, and a width W of 60.1 mm. The relevant parameters are specifically shown in Table 1.

[0131] Example 4 Group

[0132] This group of embodiments is used to verify the impact of the change of "(T×L×W) / (C1×100000)".

[0133] This group of embodiments is carried out with reference to Embodiment 2 or Embodiment 3, except that the thickness, length and width of the battery are changed, as follows:

[0134] Example 4a is carried out in accordance with Example 2, except that the thickness T of the battery is 10.5 mm, the length L is 75.9 mm, and the width W is 60.1 mm;

[0135] Example 4b is carried out in accordance with Example 3, except that the thickness T of the battery is 6.2 mm, the length L is 85.5 mm, and the width W is 64.6 mm;

[0136] The relevant parameters are shown in Table 1.

[0137] Example 5 Group

[0138] This group of examples is used to verify the impact of changes in "fluorophosphate substances".

[0139] This group of examples is carried out with reference to Example 1, except that the fluorophosphate is changed, as follows:

[0140] Example 5a, replacing the fluorophosphate from I-1 with the same mass of I-2;

[0141] Example 5b, replacing the fluorophosphate from I-1 with the same mass of I-3;

[0142] Example 5c, replacing the fluorophosphate from I-1 with the same mass of I-4;

[0143] Example 5d, replacing the fluorophosphate from I-1 with the same mass of I-5;

[0144] Example 5e, the fluorophosphate is replaced by the same mass of I-6 from I-1.

[0145] Example 6 Group

[0146] This group of examples is used to verify the impact of changes in the "mass content C1 of fluorophosphate".

[0147] This group of examples is carried out with reference to Example 1, except that the mass content C1 of the fluorophosphate is changed, as follows:

[0148] Example 6a, C1 is 0.5%, wherein C1 / C2 is about 0.042;

[0149] Example 6b, C1 is 5%, wherein C1 / C2 is about 0.42;

[0150] The relevant parameters are shown in Table 1.

[0151] Example 7

[0152] Used to verify the impact of changes in "fluorinated cyclic carbonate substances".

[0153] The same method is carried out as in Example 1, except that the fluorinated cyclic carbonate is replaced by bisfluoroethylene carbonate of the same mass from fluoroethylene carbonate.

[0154] Example 8 Group

[0155] This group of examples is used to verify the influence of the change of "mass content C2 of fluorinated cyclic carbonate".

[0156] This group of examples is carried out with reference to Example 1, except that the mass content C2 of the fluorinated cyclic carbonate is changed, as follows:

[0157] Example 8a, C2 is 5%, wherein C1 / C2 is about 0.44;

[0158] Example 8b, C2 is 20%, wherein C1 / C2 is about 0.11.

[0159] Example 9 Group

[0160] This group of examples is used to verify the impact of the change of "C1 / C2".

[0161] This group of examples is carried out with reference to Example 2 or Example 3, except that C2 is changed, as follows:

[0162] Example 9a, carried out with reference to Example 2, except that C2 is 15%, wherein C1 / C2 is about 0.067;

[0163] Example 9b is carried out with reference to Example 3, except that C2 is 6%, wherein C1 / C2 is about 0.5.

[0164] Example 10 Group

[0165] This group of embodiments is used to verify the impact of changes in the “negative electrode current collector”.

[0166] This group of examples is carried out with reference to Example 1, except that the negative electrode current collector is changed, as follows:

[0167] In Example 10a, the negative electrode current collector is: a polyethylene terephthalate film with a thickness of 1.1 μm and a copper metal layer with a thickness of 4.2 μm on both sides;

[0168] In Example 10b, the negative electrode current collector is: a polyethylene terephthalate film with a thickness of 10.2 μm and a copper metal layer with a thickness of 0.3 μm on both sides of the film.

[0169] Example 11 Group

[0170] This group of examples is used to verify the influence of the change of "the mass content of element Si in the negative electrode active material layer".

[0171] This group of examples is carried out with reference to Example 1, except that the mass content of element Si in the negative electrode active material layer is changed by adjusting the mass content of the silicon-carbon material in the negative electrode active material layer, as follows:

[0172] Example 11a, artificial graphite, silicon carbon (specific surface area of ​​3.75m 2 / g), Super P, carbon nanotubes (aspect ratio of 1523), sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 95.5:2.5:0.5:0.5:0.5:0.5; wherein the mass content of element Si in the negative electrode active material layer is 0.05%, and the thickness of the aluminum-plastic film is 35 μm;

[0173] Example 11b, artificial graphite, silicon carbon (specific surface area of ​​3.75m 2 / g), Super P, carbon nanotubes (aspect ratio of 1523), sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 75:23:0.5:0.5:0.5:0.5; wherein the mass content of element Si in the negative electrode active material layer is 10%, and the thickness of the aluminum-plastic film is 103.2μm;

[0174] Example 11c, artificial graphite, silicon carbon (specific surface area of ​​3.75m 2 / g), Super P, carbon nanotubes (aspect ratio of 1523), sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 97:1:0.5:0.5:0.5:0.5; wherein the mass content of element Si in the negative electrode active material layer is 0.02%, and the thickness of the aluminum-plastic film is 23 μm;

[0175] Example 11d, artificial graphite, silicon carbon (specific surface area of ​​3.75m 2 / g), Super P, carbon nanotubes (aspect ratio of 1523), sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 28:70:0.5:0.5:0.5:0.5; among which the mass content of element Si in the negative electrode active material layer is 30%, and the thickness of the aluminum-plastic film is 119.6μm.

[0176] Example 12

[0177] Used to verify the impact of changes in "aluminum-plastic film thickness".

[0178] The same method is carried out as in Example 1, except that the thickness of the aluminum-plastic film is changed to 22 μm.

[0179] Example 13 Group

[0180] This group of examples is used to verify the influence of the change of the "aspect ratio of the carbon nanotubes in the negative electrode conductive agent".

[0181] This group of examples is carried out with reference to Example 1, except that the aspect ratio of the carbon nanotubes is changed, as follows:

[0182] Example 13a, the aspect ratio of the carbon nanotube is 53;

[0183] In Example 13b, the aspect ratio of the carbon nanotube is 2985.

[0184] Example 14 Group

[0185] This group of examples is used to verify the impact of changes in the "specific surface area of ​​silicon-based materials".

[0186] This group of examples is carried out with reference to Example 1, except that the specific surface area of ​​silicon carbon is changed, as follows:

[0187] Example 14a, the specific surface area of ​​silicon carbon is 0.48 m 2 / g;

[0188] Example 14b, the specific surface area of ​​silicon carbon is 11.7 m 2 / g.

[0189] Embodiment 15

[0190] Used to verify the impact of changes in "T / L".

[0191] The same method is carried out as in Example 1, except that the length L of the battery is changed to 150 mm (the thickness and width of the battery remain unchanged). The relevant parameters are shown in Table 1.

[0192] Example 16

[0193] Used to verify the impact of changes in "T / W".

[0194] The same procedure is carried out as in Example 1, except that the width W of the battery is changed to 115 mm (the length and thickness of the battery remain unchanged). The relevant parameters are shown in Table 1.

[0195] Embodiment 17

[0196] This group of embodiments is used to verify the impact of changes in "battery size".

[0197] This group of examples is carried out with reference to Example 1, except that the length, width and thickness of the battery are changed, as follows:

[0198] In Example 17a, the thickness T of the battery is 2.2 mm, the length L is 25.6 mm, and the width W is 15.3 mm;

[0199] In Example 17b, the thickness T of the battery is 11.9 mm, the length L is 150.2 mm, and the width W is 120.2 mm; the relevant parameters are specifically shown in Table 1.

[0200] Table 1

[0201]

[0202]

[0203] Comparative Example 1

[0204] The process is carried out in accordance with Example 1, except that no fluorophosphate is added to the electrolyte.

[0205] Comparative Example 2

[0206] Refer to Example 1, except that the size of the battery is changed. Specifically, the battery thickness T is 8.5 mm, the length L is 50 mm, the width W is 45 mm, T / L is 0.17, T / W is 0.189, and (T×L×W) / (C1×100000) is 8.7.

[0207] Comparative Example 3

[0208] Refer to Example 1, except that the size of the battery is changed. Specifically, the thickness T of the battery is 8.5 mm, the length L is 120.2 mm, the width W is 30 mm, T / L is 0.071, T / W is 0.283, and (T×L×W) / (C1×100000) is 13.9.

[0209] Comparative Example 4

[0210] Refer to Example 1, except that the size of the battery and the mass content C1 of the fluorophosphate are changed. Specifically, the thickness T of the battery is 12 mm, the length L is 150 mm, the width W is 120 mm, and C1 is 1%; T / L is 0.08, T / W is 0.1, and (T×L×W) / (C1×100000) is 432.

[0211] Comparative Example 5

[0212] Refer to Example 1, except that the size of the battery and the mass content C1 of the fluorophosphate are changed. Specifically, the thickness T of the battery is 2 mm, the length L is 25 mm, the width W is 15 mm, and C1 is 5%; T / L is 0.08, T / W is 0.133, and (T×L×W) / (C1×100000) is 0.2.

[0213] Test Case

[0214] (1) High temperature cycle test

[0215] The batteries prepared in the examples and comparative examples were placed in an oven (temperature of 45°C ± 2°C), and charged to 4.48V (cut-off current of 0.25C) at a current density of 1.5C. After the batteries were fully charged, they were left for 5 minutes, and then discharged at a current density of 0.5C (cut-off voltage of 3.0V). The discharge capacity was recorded as the initial capacity Q1. When the cycle reached 700 cycles, the last discharge capacity Q2 of the battery was recorded. The capacity retention rate (%) = Q2 / Q1 × 100%. The results are recorded in Table 2.

[0216] (2) High temperature storage test

[0217] The batteries prepared in the examples and comparative examples were charged to 4.48V at 0.7C (cut-off current was 0.25C), and the storage thickness B1 was tested after being left for 2 hours. They were placed in an oven (temperature of 85°C±2°C) and stored for 8 hours. After the batteries returned to room temperature (25°C±2°C), the final thickness B2 was tested. The high-temperature storage expansion rate (%) = B2 / B1×100%. The results are recorded in Table 2.

[0218] (3) Furnace temperature test

[0219] The batteries prepared in the examples and comparative examples were fully charged at room temperature (25°C±2°C), then placed horizontally in an oven, and the oven was heated to 130°C-135°C at a heating rate of (5±2)°C / min, and placed at this temperature for 60 minutes; the battery status was observed after standing for 2 hours; the battery was judged to have passed when there was no leakage, no fire, and no explosion. Ten samples were tested for each example, and the results are recorded in Table 2.

[0220] (4) Acupuncture test

[0221] The batteries prepared in the examples and comparative examples were fully charged at room temperature (25°C ± 2°C) and tested at a speed of 100 mm / sec using a 2.5 mm stainless steel needle to the center of the battery. The needle penetrated the battery in a direction perpendicular to the battery plate and remained in the battery. The battery status was recorded. The battery passed if it did not catch fire or explode. Ten samples were tested for each example and the results are recorded in Table 2.

[0222] (5) Overcharge test

[0223] The batteries prepared in the examples and comparative examples were charged to 4.48V+0.2V at room temperature (25°C±2°C) using the maximum current constant current, and then kept at this voltage for 7 hours, and the battery status was recorded. The battery passed if it did not catch fire or explode. Ten samples were tested for each example, and the results are recorded in Table 2.

[0224] (6) Lithium deposition test

[0225] The batteries prepared in the examples and comparative examples were placed at -3°C for 4 hours, fully charged at 0.1C, cut off at 0.025C, placed at rest for 10 minutes, and then discharged to 3V at 0.2C, for 25 cycles. Subsequently, the batteries were placed at room temperature (25°C) for 4 hours, fully charged at 0.1C, and dissected. When the lithium deposition area was ≤3%, it was considered passed. Ten samples were tested for each example, and the results are recorded in Table 2.

[0226] Table 2

[0227]

[0228]

[0229] It can be seen from Table 2 that the battery of the present invention has higher cycle stability and safety performance than the comparative example.

[0230] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A battery, characterized in that: The battery includes an electrolyte, the electrolyte includes a fluorophosphate ester, and the structural formula of the fluorophosphate ester is wherein R1, R2 and R3 are each independently selected from at least one of the following groups which are substituted or unsubstituted with fluorine: alkyl, alkenyl, alkynyl and phenyl, and the total number of fluorine substituents in R1, R2 and R3 is ≥3; The ratio T / L of the thickness T of the battery to the length L of the battery is 0.05-0.15; the ratio T / W of the thickness T of the battery to the width W of the battery is 0.07-0.2; The length L of the battery is in mm, the width W is in mm, the thickness T is in mm and the mass content C1 of the fluorophosphate in the electrolyte satisfies: 0.3≤(T×L×W) / (C1×100000)≤200.

2. The battery according to claim 1, wherein 11≤(T×L×W) / (C1×100000)≤50; preferably, 15≤(T×L×W) / (C1×100000)≤45; and / or, T / L is 0.7-0.14; And / or, T / W is 0.08-0.

18.

3. The battery according to claim 1 or 2, wherein: The thickness T of the battery is 2-12, in mm; And / or, the length L of the battery is 20-220, in mm; And / or, the width W of the battery is 15-125, in mm; And / or, the mass content C1 of the fluorophosphate in the electrolyte is 0.5%-5%; preferably 1%-3%.

4. The battery according to claim 1 or 2, wherein R1, R2 and R3 are each independently selected from at least one of the following fluorine-substituted groups: an alkyl group having 1 to 3 carbon atoms, an alkenyl group having 2 or 3 carbon atoms, an alkynyl group having 2 or 3 carbon atoms, and a phenyl group; Preferably, the fluorophosphate comprises At least one of .

5. The battery according to claim 1 or 2, wherein The battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector; the negative electrode current collector comprises a polymer layer and a metal layer located on both sides of the polymer layer; Preferably, the polymer layer comprises at least one of polypropylene, polyethylene, polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polyvinyl chloride, polyethylene terephthalate, polypropylene and polyimide; the metal layer comprises copper; Preferably, the thickness of the polymer layer is 1 μm-10.5 μm; the thickness of the metal layer is 0.3 μm-4.5 μm.

6. The battery according to claim 1 or 2, wherein: The battery further comprises a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising element Si, the mass content of element Si in the negative electrode active material layer is 0.02%-50%; preferably 0.02%-30%; more preferably 0.05%-10%; The battery further comprises an aluminum-plastic film, and the thickness of the aluminum-plastic film is 20 μm-120 μm, preferably 35 μm-105 μm.

7. The battery according to claim 1 or 2, wherein: The battery further comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode conductive agent, the positive electrode conductive agent comprises carbon nanotubes, and the aspect ratio of the carbon nanotubes is 50-3000; preferably 500-2500; And / or, the battery further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode conductive agent, the negative electrode conductive agent comprises carbon nanotubes, and the aspect ratio of the carbon nanotubes is 50-3000; preferably 500-2500.

8. The battery according to claim 1 or 2, wherein: The battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a silicon-based material; the silicon-based material comprises at least one of silicon-carbon, silicon-oxygen, nano-silicon and silicon alloy; Preferably, the specific surface area of ​​the silicon-based material is 0.4 m 2 / g-15m 2 / g; more preferably 2m 2 / g-5m 2 / g.

9. The battery according to claim 1 or 2, wherein: The electrolyte further comprises a fluorinated cyclic carbonate, the mass content of the fluorinated cyclic carbonate in the electrolyte is C2, and C1 / C2 is 0.04-0.5; preferably 0.15-0.

2.

10. The battery according to claim 1 or 2, wherein The electrolyte also includes an organic solvent, a lithium salt and an additive; The organic solvent comprises a carbonate solvent and / or a carboxylate solvent, wherein the carbonate solvent comprises ethylene carbonate and at least one of the following fluorine-substituted or unsubstituted solvents: propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; the carboxylate solvent comprises at least one of propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, propyl propionate, ethyl propionate and methyl butyrate; The lithium salt comprises at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide and lithium tetrafluoroborate; The additive includes at least one of ethylene glycol bis(propionitrile) ether, adiponitrile, succinonitrile, 1,3,6-hexanetrinitrile, glutaronitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,3,4,5,6-(2-cyanoethoxy)hexane, 1,3-propane sulfonate, propylene-1,3 sulfonate and vinyl sulfite.

Citation Information

Patent Citations

  • Battery

    CN109428078A

  • Lithium secondary battery electrolyte capable of reducing battery impedance and lithium secondary battery

    CN110148776A

  • Lithium ion battery

    CN116093428A

  • Lithium ion battery

    CN116315090A

  • Secondary battery and electric device

    CN117121256A